A Cambrian–Ordovician Terrestrialization of Arachnids - Lozano-Fernandez, Jesus; Tanner, Alastair R.; Puttick, Mark N.; Vinther, Jakob; Edgecombe, Gregory D.; Pisani, Davide (Frontiers in Genetics, 2020)
Understanding the temporal context of terrestrialization in chelicerates depends on whether terrestrial groups, the traditional Arachnida, have a single origin and whether or not horseshoe crabs are primitively or secondarily marine. Molecular dating on a phylogenomic tree that recovers arachnid monophyly, constrained by 27 rigorously vetted fossil calibrations, estimates that Arachnida originated during the Cambrian or Ordovician. After the common ancestor colonized the land, the main lineages appear to have rapidly radiated in the Cambrian-Ordovician boundary interval, coinciding with high rates of molecular evolution. The highest rates of arachnid diversification are detected between the Permian and Early Cretaceous. A pattern of ancient divergence estimates for terrestrial arthropod groups in the Cambrian while the oldest fossils are Silurian (seen in both myriapods and arachnids) is mirrored in the molecular and fossil records of land plants. We suggest the discrepancy between molecular and fossil evidence for terrestrialization is likely driven by the extreme sparseness of terrestrial sediments in the rock record before the late Silurian.